The Role of the Public Administration in Protecting the Environment from Pollution - ALHENDI, Noor; SALAMEH, Muamar Hasan (Journal of Environmental Management and Tourism, 2022)
The environment is the vital medium in which man lives, so it has become the focus of human societies' interest to provide a safe environment for individual living, and the rapid growth and expansion of human societies and the prosperity of industries that generate problems in the environment, including pollution. Hence, interest in the problem of environmental pollution began, which created mechanisms to protect the environment, and there became international and regional agreements in this regard, which created interest in the existence of legislative mechanisms regulating the protection of the environment and occupied a high position as the legal means that simplifies protection for the environment and is considered the legal reference in setting general policies to protect the environment from The danger of pollution and the protection of humans and the environment from its harmful effects. Since the administration is considered to have the largest and most important role in protecting the environment, with its general powers granted to it by legislation to preserve the environment and deter violators. This study came to show the means of administrative control in protecting the environment from types of pollution and was limited to the means of administrative control in protecting the environment from pollution.